(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Website is a need to be very important to create an online presence for individuals, businesses, companies, and education. By using website, everyone can be better to known and widely known on the internet. However, some users still think that having a website should prepare many things, ranging from cost to good coding skills. The presence of the Google company in the world of technology provides convenience through its products. Google Sites is one of the platforms that provides services to make it easier to create the websites that are used as objects of training activities with workshop activity partners by Master Program of Informatics Universitas Ahmad Dahlan and SMK Muhammadiyah Banjar. The purpose of this community service activity is to carry out training on the use of Google Sites in creating portfolios and learning media. The audience of service is teachers and students with a total of 27 participants from SMK Muhammadiyah Banjar West Java Province. The activity was carried out on August 24, 2022. The stages of the activity were preparation, implementation, and evaluation. Preparation is carried out by conducting a pre-test survey of trainees. The implementation is carried out with training and hands on implementation of website creation for each participant. Evaluation of activities is carried out for each stage by collecting post-test from each trainee. The result of the activity is to increase the knowledge of training participants, both students and teaching staff in overcoming problems in the world of technology so as to make it easier to adapt to the industrial world. The training carried out received a very good response with the score of 79.13% stating that they strongly agreed with the advantages of this training.concept of healthy elderly people related to the pandemic.